Free-Radical-Involved Trifluoromethylthiolation Cyclization of Alkenes To Access SCF3-Substituted Indolo[2,1-a]isoquinolines - Li, Yang; Li, Lijun; Yan, Qinqin; Ren, Yingming; Li, Xuan; Liu, Zhong-Quan; Li, Zejiang (Synlett, 2022)
Free-radical-promoted tandem trifluoromethylthiolation of alkenes with AgSCF3, which provides an efficient protocol for the construction of SCF3-modified indolo[2,1-a]isoquinolines with moderate to good yields. A series of scaled-up experiments, other substrate transformations, and radical inhibition experiments were operated to verify the merit of this reaction system.
Keywords: trifluoromethylthiolation; tandem cyclization; alkenes; AgSCF3; indolo[2,1-a]isoquinolines